Angiomatoid variant of fibrous histiocytoma: a case report and review of literature - R. PRATIBHA, & S. AHMED (Paediatric Dentistry, 2006)
Fibrous histiocytomas by themselves are not very common in the head and neck region. Apart from considering the above fact, this report describes a unique and relatively rare variant of the neoplasm – the angiomatoid fibrous histiocytoma (AFH) which has a characteristic appearance and predilection for young individuals that occurred in the left lower border of the mandible in a 13-year-old girl.